(3NHQ GdeHJOCs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ef Ydi ef WdH GdYde HeQGOghHYO agPg fHPI PcQJ ajgG ChGFd MGdi , heHGOF ETJZGdi (B,(3SejJgG NHQ GdeHJOC s
(3BNQgG (B:s
(3LYdfG Gddg eef cfa GdYde ai hGbjI hGbjI , hYaG Yef Sda hNJe HNjQ ai YGajI , hGdMeO ddg QH GdYGdejf GfJgi NHQ ai YGajI , hGdMeO ddg QH GdYGdejf GfJgi NHQ GdeHJOC s
(3Vef eLehY , JQJjHgG (B: (3ef U (B157 - (3U(B165s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa ecJHI eMSf Hf LYaQ Hhfei GdNGUI (B((3JUha (B377) s
Keywords: (3GdJGQjNs